RFID-Qualifikation in der Logistikpraxis - Sascha Bioly; Matthias Klumpp (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2010)
– The technology of RFID (Radio Frequency Identification) is one of the major developments in logistics and supply chain management enhancing transparency for all partners in global transport processes. This paper aims at the basic description of core elements and success factors of this technology in order to enable an in-depth discussion and concept for qualification concepts in this area. Together with the general education development of integrated qualifications frameworks the authors draft a RFID qualifications framework adapted to different working areas and qualifications levels in logistics. This could be used for companies in this industry to easily adapt their qualification needs regarding RFID depending on different contexts and objectives.
Keywords: 650; Transportlogistik; Lieferkette; IT-gestützte Logistik; RFID; Qualifikation